OCCLUSAL OUTCOME OF NON-EXTRACTION AND ALL FIRST PREMOLARS EXTRACTION TREATMENT IN PATIENTS WITH CLASS-I MALOCCLUSION - Kamal, Adeel Tahir; Shaikh, Attiya; Fida, Mubassar (Journal of Ayub Medical College Abbottabad, 2016)
Background: Class-1 malocclusion commonly presents with crowding and poses an aesthetic concern to patients. An orthodontist may encounter a variety of dental problems and must handle them strategically to establish adequate occlusal relationships. Hence, this study was conducted to evaluate the occlusal characteristics of patients who have undergone non-extraction or all first premolars extraction treatment for class I malocclusion using the peer assessment rating (PAR) index. Methods: The pre-treatment and post treatment dental casts of 94 subjects with class-I malocclusion were retrospectively screened. The sample was distributed into two groups, i.e., non-extraction and all first premolars extraction groups. The Mann Whitney-U test was used to compare the mean percentage improvement in the PAR scores between the two groups. A p-value of ‰¤0.05 was considered statistically significant. Results: The mean percentage improvement in the non-extraction group was 74.28% in the non-extraction group and 74.5% in the all first premolars extraction group. A significant difference (p=0.04) was found between the pre-treatment PAR scores for the two treatment modalities. There was no significant difference between the post treatment PAR scores (p=0.45) and the mean percentage improvement in PAR scores (p=0.41) between the treatment groups. Conclusions: The improvement in occlusal characteristics in patients who underwent non-extraction treatment and all first premolar extraction treatment was comparable as assessed through mean percentage improvement in PAR scores. Keywords: Angle class I; Index; Occlusion; Malocclusion